2022
DOI: 10.3168/jds.2021-21634
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Student Literature Review: Enterotoxigenic potential and antimicrobial resistance of staphylococci from Brazilian artisanal raw milk cheeses

Abstract: More than 30 types of artisanal cheeses are known in Brazil; however, microorganisms, such as Staphylococcus spp., can contaminate raw milk cheeses through different sources, from milking to processing. Staphylococcal food poisoning results from the consumption of food in which coagulase-positive staphylococci, mostly Staphylococcus aureus, have developed and produced enterotoxins. In addition, an emerging public health concern is the increasing antimicrobial resistance of some Staphylococcus strains. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 87 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Cheeses with Positive Culture at D0 and DE Among the Belgian cheeses that were included in this study, 10 different varieties were contaminated with CPS (threshold 100 CFU/g). Notably, this represents a lower prevalence than previously observed in artisanal cheeses from raw milk in Brazil, reported in the review by Carneiro Aguiar et al [13]. The 30 cheese varieties were more contaminated at D0 (n = 8) than at DE (n = 6), and four varieties were contaminated at both D0 and DE.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Cheeses with Positive Culture at D0 and DE Among the Belgian cheeses that were included in this study, 10 different varieties were contaminated with CPS (threshold 100 CFU/g). Notably, this represents a lower prevalence than previously observed in artisanal cheeses from raw milk in Brazil, reported in the review by Carneiro Aguiar et al [13]. The 30 cheese varieties were more contaminated at D0 (n = 8) than at DE (n = 6), and four varieties were contaminated at both D0 and DE.…”
Section: Resultsmentioning
confidence: 48%
“…Notably, S. aureus is one of the main causative agents of mastitis in dairy ruminants, and thus, such infections may represent a potential source of this pathogen in dairy products [8]. Indeed, several studies have reported high prevalences of CPS [9][10][11][12][13], especially S. aureus [10,11], in raw milk and raw-milk cheeses. In addition, dairy products can be contaminated by S. aureus during processing due to human carriers and poor hygiene practices [14].…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus and E. coli are globally recognized as significant zoonotic pathogens that can lead to bacterial infections and foodborne illnesses [ 23 ]. These microorganisms have been detected in various food sources such as chicken meat, eggs, beef, sheep and goat meat, buffalo meat, raw bovine milk, raw sheep’s and goat’s milk, raw buffalo milk, cheese, and fish [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. In Brazil, the Health Surveillance Secretariat reported 2504 outbreaks of foodborne diseases between 2016 and 2019, affecting 37,247 individuals and resulting in 38 deaths.…”
Section: Resultsmentioning
confidence: 99%
“…aureus and E. coli are globally recognized as significant zoonotic pathogens that can lead to bacterial infections and foodborne illnesses [23]. These microorganisms have been detected in various food sources such as chicken meat, eggs, beef, sheep and goat meat, buffalo meat, raw bovine milk, raw sheep's and goat's milk, raw buffalo milk, cheese, and fish [24][25][26][27][28][29][30][31]. In Brazil, the Health Surveillance Secretariat reported 2504 outbreaks of foodborne diseases between 2016 and 2019, affecting 37,247 individuals and resulting in 38 deaths.…”
Section: Microbiological Quality Of Cheese Samplesmentioning
confidence: 99%